Efektivitas Sosialisasi Politik Pemilihan Umum Legislatif Tahun 2014 oleh Komisi Pemilihan Umum - Djuyandi, Yusa (Bina Nusantara University, 2014)
Based on data from the Election Commission, the number of public participation in the elections of 2004 was 84%, while at the elections of 2009 the number of participation decreased to 71%. The declining participation shows increasing number of participants who did not vote or abstain. This phenomenon needs to be taken seriously by the Election Commission to conduct intensive socialization. The purpose of this study was to analyze the effectiveness of political socialization in the 2014 legislative elections by the Election Commission. The research method used was a qualitative method, the research data consists of primary and secondary data. Primary data is done through observation and interview techniques. Results and Discussion revealed that political socialization is very important. KPU socialization process, not just invite people to come to the polling stations (TPS), but also urge people to maintain order and the smooth running of the 2014 election. Commission was targeting 75% of community participation, and based on the results of the final calculation, the data shows the number of public participation is 75.11%. The conclusion of this study is the Commission has successfully reached its target in suppressing the number of abstain, and this shows that the Commission has effectively conduct political socialization.